LEGAL PROTECTION FOR VICTIMS OF MURDER COMMITTED BY CHILDREN: A PERSPECTIVE OF THE INDONESIAN CHILD PROTECTION LAW - Yoga Pramudyas Putra; Prof. Dr. Sadjijono Sadjijono (YURIS: Journal of Court and Justice, 2025)
Murder is a legal crime with the most serious criminal threat as regulated in the Criminal Code (KUHP) Article 338 KUHP and Article 340 KUHP for premeditated murder. Data from the Ministry of Women's Empowerment and Child Protection shows that 4% of children are perpetrators of criminal acts in murder cases. The Constitution of the Republic of Indonesia has outlined that every person has the right to legal recognition, provisions and protection. Legal protection given to children as perpetrators and victims as injured parties must be carried out in order to create legal certainty, the usefulness of the law and legal justice. The research method used is the normative juridical legal research type. This thesis analysis results that legal protection is provided to child perpetrators and victims through the victim's family during the investigation process until the court decision. This is done to protect the rights of victims and children as perpetrators of murder fairly. Responsibility for children as perpetrators of murder is given by the court in accordance with the Child Protection Law with a maximum sentence of ½ (one half) of the maximum sentence punishable against an adult.